The Effect of Number of Audit Committee Meetings, Company Size, Leverage and Managerial Ownership on Financial Reporting Fraud in Service Companies on the IDX - Jessica Audrey Theofani Larune; Verawati Gita Sari Harahap; Ida Rohana Silaban; Arie Pratania Putri (Jurnal Mantik, 2021)
The study was conducted to understand the effect of the variable number of audit committee meetings, company size, leverage, and managerial ownership on financial reporting fraud. Financial reporting fraud is obtained by using the Beneish M-score index. While the population is taken from service companies in the service, trade and investment sub-sector which are listed on the IDX in 2017-2019. The research was conducted using quantitative methods with purposive sampling technique with a total sample of 96 data and data analysis using logistic regression analysis. From the data processing, it was concluded that only one independent variable was managerial ownership which had an effect on the dependent variable while the other three independent variables (number of audit committee meetings), firm size, leverage) does not have a significant effect on the dependent variable.